Inspección de una losa de 70 años de un edificio en el Golfo de México - Castro-Borges, P.; Balancán-Zapata, M.; López-González, A.; Córdova-Quintal, M. (Revista ALCONPAT, 2014)
The Progreso pier has a head which is a seventy year-old building that is exposed to anaggressive environment in the Gulf of Mexico. As a consequence of the chloride exposureand lack of maintenance, the slabs have shown strong deterioration symptoms. A previousstructural inspection suggested a very expensive and non well understood method to repairthe slab, which made the authorities to think about demolition in spite of the collateraldamage to other elements like columns and beams. Because of the deterioration level, theauthors of this paper suggested a second inspection before demolishing and it was performedon selected parts of the slab. The objective of this work is to discuss details and results of thisand previous inspection and diagnosis. The new diagnosis indicated the need of demolishingspecific parts of the lower concrete cover of the slab and the substitution of the reinforcementby CFRP.Keywords: inspection, repair, chlorides, electrochemical techniques